Multilayer Laue Lens: A Path Toward One Nanometer X-Ray Focusing. (27th September 2010) - Yan, Hanfei; Kang, Hyon Chol; Conley, Ray; Liu, Chian; Macrander, Albert T.; Stephenson, G. Brian; Maser, Jörg
Abstract : The multilayer Laue lens (MLL) is a novel diffractive optic for hard X-ray nanofocusing, which is fabricated by thin film deposition techniques and takes advantage of the dynamical diffraction effect to achieve a high numerical aperture and efficiency. It overcomes two difficulties encountered in diffractive optics fabrication for focusing hard X-rays: (1) small outmost zone width and (2) high aspect ratio. Here, we will give a review on types, modeling approaches, properties, fabrication, and characterization methods of MLL optics. We show that a full-wave dynamical diffraction theory has been developed to describe the dynamical diffraction property of the MLL and has been employed to design the optimal shapes for nanofocusing. We also show a 16 nm line focus obtained by a partial MLL and several characterization methods. Experimental results show a good agreement with the theoretical calculations. With the continuing development of MLL optics, we believe that an MLL-based hard x-ray microscope with true nanometer resolution is on the horizon.